The jealousy in the triadic relations of friendship - Shostak, Liudmila A.; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article reveals the notion of friendly jealousy, jealousy in triadic friendships (the same-sex and different-sex friendship), including three subjects of relations: a jealous individual, a relationship partner and a competitor. A social triangle of jealousy is described: primary (basic), secondary and tertiary (competing, unfavorable) relationships. Classifcation of situations of jealousy in triadic friendly relations is presented: partners and a competitor of the same sex; partners of the same sex and a competitor of different sex with a jealous individual; partners of different sexes and a competitor of one sex with a jealous individual; partners of different sexes and a competitor of the opposite sex with a jealous individual.